Application of Six Sigma management in infection control in the operating room (六西格玛管理在手术室感染控制中的应用效果) - XU Xu (徐旭); REN Guqun (任顾群); WANG Yuena (刘建荣); LIU Jianrong (高燕); GAO Yan (王小洁); WANG Xiaojie (许远乐) (中西医结合护理, 2023)
Objective To investigate the effect of Six Sigma projects in the management of operating room, and to provide effective reference for reducing infection in the operating room. Methods A total of 100 patients who received surgical treatment from January 2022 to December 2022 were selected into the experimental group, and Six Sigma Management was applied to the daily surgical management. Another 100 patients who received surgical treatment from January 2021 to December 2021 were selected and into the control group. The occurrence of surgical error, iatrogenic infection, massive hemorrhage during and after operation and patient satisfaction were compared between the two groups. Results The incidences of surgical error, iatrogenic infection, massive hemorrhage during and after operation in the study group were lower than those in the control group respectively(P＜0. 01). Satisfaction rate in the observation group was higher than that in the control group(P＜0. 01). Conclusion Application of Six Sigma projects could effectively reduce the risk of operation error, iatrogenic infection and massive bleeding during and after operation, improve patient satisfaction and the management efficiency in the operating room. (目的 评价分析在手术室管理工作中运用六西格玛管理观念的效果价值, 为减少手术室感染提供有效的参考依据。方法 选取医院手术室2022年1月—12月收治拟行手术治疗患者100例纳入研究组, 将六西格玛管理运用于手术室日常工作之中; 选取2021年1月—12月行手术治疗的患者100例, 设为对照组, 手术室日常工作中运用常规管理方式。对两组手术差错发生情况、医源性感染发生情况、术中及术后大出血发生情况以及患者满意度评分结果进行比较。结果 研究组手术差错、医源性感染、术中与术后大出血发生率均低于对照组, 差异有统计学意义(P＜0. 01), 研究组满意率高于对照组(P＜0. 01)。结论 手术室管理中运用六西格玛管理方法, 能有效降低手术差错、医源性感染、术中及术后大出血发生风险, 提高患者满意度, 持续改善手术室管理工作效率。)